ANALISIS KANDUNGAN PROTEIN DAN SIFAT ORGANOLEPTIK NUGGET IKAN CAKALANG DENGAN JENIS TEPUNG YANG BERBEDA - Febriana Muchtar (Universitas Pahlawan Tuanku Tambusai, 2022)
Skipjack fish is one type of fish as a source of quality animal protein. Skipjack fish can be processed into various f food products, one product is a fish nugget. This study aimed to determine the effect of using a different type of flour in the making of skipjack nuggets on the protein content and organoleptic properties of skipjack nuggets. This research was conducted by using an experimental method with non-factorial Completely Randomized Design (CRD). The treatment applied was the use of different types of flour in the making of nuggets, namely corn flour (TC1), tapioca flour (TC2), and wheat flour (TC3). Each treatment was made 3 times replication. Protein content was analyzed by semi-micro Kjedhal method and organoleptic properties by using the hedonic test (level of preference). Data analysis was conducted by using the Analysis of Variance (ANOVA) method and was followed by Duncan’s Multiple Range Test (DMRT) test if there was a significant difference between treatments. The result of the research shows that the type of flour had a significant effect on protein content and organoleptic properties of nuggets, namely texture, and taste, but had no significant effect on the color and aroma of nuggets. The best treatment was obtained by using wheat flour with the highest protein content of 20.87% and organoleptic properties of color 4.40 (like), aroma 4.44 (like), texture 4.44 (like), and taste 4.40 (like). Keywords: Skipjack fish, nuggets, protein, and organoleptic properties